Preliminary results on feeding habits of the invasive fish Fistularia commersonii (Ruppell, 1862) in the coast of Benghazi, Libya - Bashir , Asma; Elbaraasi, Houssein (Libyan Journal of Science &Technology, 2022)
The feeding habits of the exotic fish Fistularia commersonii off the coast of Benghazi, Libya were investigated. A total of 189 specimens were collected throughout the year of 2012-2013. The mean total length (TL) and mean weight was 99.08±6.45cm and 545.33±116 g, respectively. The condition factor (K) ranged between 0.7 and 0.8. Fish were found in large quantities (87%) in the stomach of the blue-spotted cornet fish. While crustaceans (2%) and mollusks (1%). The results showed also that F. commersonii feeds on prey from diverse habitats as well as depths.